PENGARUH PENGALAMAN PRAKTIK KETERAMPILAN MENGAJAR (PKM) DAN LINGKUNGAN KELUARGA TERHADAP MINAT MENJADI GURU YANG DIMEDIASI OLEH EFIKASI DIRI - Wulandari, Arista; Mardi; Handarini, Dwi (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
This study aims to determine the effect of teaching skill practices (PKM) experience and the family environment on the interest in becoming a teacher through mediation of self-efficacy in education students at the Faculty of Economics, State University of Jakarta Class of 2019. The type of research is explanatory survey research with a quantitative approach. Data was collected through a research instrument using a questionnaire. The analysis method is path analysis with the SPSS 25 application. The results of the study are: (1) PKM experience has a positive effect on interest in becoming a teacher, (2) Family environment has a positive effect on interest in becoming a teacher, (3) PKM experience has a positive effect on self-efficacy, (4) Family environment has a positive effect on self-efficacy, (5) Self-efficacy has a positive effect on the interest in becoming a teacher, (6) Self-efficacy can mediate the PKM experience on the interest in becoming a teacher, (7) Self-efficacy cannot mediate the PKM experience on the interest in becoming a teacher.